Experimental and Numerical Analysis of Plate Heat Exchanger Performance with Modified Chevron Angle Geometry: Effects on Heat Transfer Coefficient and Pressure Drop - Rahmad, Rahmad (SEAN Institute, 2025)
Plate heat exchangers (PHEs) are widely utilized in industrial thermal management systems due to their compact design and high thermal efficiency. The optimization of chevron angle geometry plays a crucial role in enhancing heat transfer performance while managing pressure drop constraints. This comprehensive study presents an experimental and numerical investigation of PHE performance characteristics with modified chevron angle configurations ranging from 30° to 75°. Experimental procedures utilized water-to-water heat transfer systems with temperature measurement accuracy of ±0.1°C and pressure differential transducers calibrated to ±0.25%. Reynolds numbers were varied between 500 and 2500 to capture both laminar and turbulent flow regimes. Computational Fluid Dynamics (CFD) simulations employing ANSYS Fluent with realizable k-ε turbulence models were conducted with mesh element densities exceeding 14.8 million elements to ensure grid independence. Results demonstrate that the overall heat transfer coefficient increases by approximately 21% when chevron angle increases from 60° to 120°, while friction factors exhibit non-linear variation patterns across different Reynolds number ranges. The Nusselt number correlations developed from experimental data show strong correlation coefficients (R² > 0.95) with published empirical models. Pressure drop analysis reveals that lower chevron angles (30°) impose 2.5 times greater pressure drop penalties compared to higher angles (60°-75°) at equivalent Reynolds numbers. Modified geometry configurations demonstrated thermal enhancement factors ranging from 1.15 to 1.68 depending on operational parameters. These findings establish a scientific foundation for optimal plate heat exchanger design in applications requiring balanced thermal performance and hydraulic efficiency, with significant implications for energy conservation in industrial heat recovery systems.